PENGARUH KINERJA GURU PENDIDIKAN AGAMA ISLAM TERHADAP HASIL BELAJAR SISWA - Mustafa (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
The ability to manage a person's level of success in carrying out tasks in accordance with the responsibilities called teacher performance that must be possessed by all teachers in carrying out their duties so that the teaching and learning process can be carried out effectively, efficiently and even the implementation can be carried out in a conducive manner so that it has the expected results. A teacher is very influential in the creation of quality educational processes and outcomes. The role of Islamic Religious Education teachers has quite a big influence in improving the quality of learning. Those who have competence in teaching, it is possible that they will be able to generate interest in their students' learning in participating in teaching and learning activities. On the other hand, if the teacher lacks competence, it will cause obstacles in the process of teaching and learning activities in the classroom, because the teacher will be faced with situations and conditions that are less conducive, because students have heterogeneous attitudes and behaviors in receiving lessons. For this reason, the role of an Islamic Religious Education teacher participates in providing enlightenment for his students at school. Of the several factors that affect the level of student achievement and it also determines the success or failure of students in the teaching and learning process in addition to the teacher's role, is student interest in learning. In teaching and learning activities, interest is a person's tendency towards an object or an activity that is favored accompanied by feelings of pleasure, attention and activeness to do. the teacher's role in increasing students' interest in learning in PAI subjects, it can be concluded that the three roles of the teacher as educators, coaches and supervisors have been carried out, proving that the teacher's role greatly influences the increasing interest of students in PAI learning.